Occurrence and toxicological assessment of selected active pharmaceutical ingredients in effluents of pharmaceutical manufacturing plants and wastewater treatment plants in Kampala, Uganda - Kayiwa, R.; Kasedde, H.; Lubwama, M.; Kirabira, J. B.; Kayondo, Timothy (Water Practice & Technology, 2022)
There is an increasing eco-toxicological risk associated with pharmaceuticals globally. The prevalence of six active pharmaceutical ingredients (APIs) was studied in effluents of three pharmaceutical manufacturing plants (PMPs) and two wastewater treatment plants (WWTPs) in Kampala, Uganda to ascertain the removal potentials for APIs. The APIs include atenolol, losartan, carbamazepine, sulfamethoxazole, clarithromycin, and diclofenac. The APIs were extracted using solid-phase extraction cartridges and concentrations were analyzed using a liquid chromatography-mass spectrometer system. The concentration ranges of the APIs were <limit of detection (LOD), <LOD – 4.75, <LOD – 1.37, <LOD – 1.17, and 0.28–19.55 mgL−1 for losartan, diclofenac, sulfamethoxazole, carbamazepine, and clarithromycin respectively in effluents of WWTPs, whereas in treated wastewater from PMPs concentrations were 0.00, 0.00–0.23, 5.30–7.4, 0.00–0.14, and 0.12–4.53 mgL−1 for losartan, diclofenac, sulfamethoxazole, carbamazepine, and clarithromycin respectively. The API removal efficiency of PMPs was higher than WWTPs with some APIs removed to concentrations of <LOD. The range of hazard quotients (HQs) for APIs was 0.018–0.9775000 with most of the APIs posing remarkably high environmental risks at HQs way greater than 1. Only sulfamethoxazole from the effluents of Lubigi WWTP, Bugolobi WWTP, and PMP C posed low risks with HQs of <1 at 0.018, 0.305, and 0.018 respectively. The high HQs for most APIs imply that immediate recipients are at very high toxicological risks, yet most studies have focused on the final destinations of APIs in environments where toxicological risks are often minimal due to dilution effects.
Keywords: Wastewater treatment plants; Risk assessment; Active pharmaceutical ingredients; Pharmaceutical manufacturing plants